The Incorporation Of America - Culture And Society In The Gilded Age - Screws, Raymond (Teaching History: A Journal of Methods, 2007)
Any era in American history can be viewed as pivotal, but the time period that The Incorporation of America covers was truly a time of change that reached the country's core. The one thing that has changed about this book, which covers Gilded Age culture and society, is that it is more relevant today and has evolved into a classic. In the new "Preface" to this 25th Anniversary Edition, Alan Trachtenberg writes that "My focus was not only on change but also on conflict and contradiction." But the author also explains that the book "describes the origins of our own times."